(untitled) ("Temas Sociais" Journal, 2023)
Interview with Begoña Vigo Arrazola by Hélia Bracons and Jacqueline Marques Project Inclusive Practices of Creative and Innovative Teaching, using Information and Communication Technologies in Information and Communication Technologies in Inclusive Education Schools - PIECIT PIECIT is a program that integrates creative and innovative teaching practices, using information and communication technologies, in information and communication technologies in inclusive schools. It is a project, with the support of the Erasmus+ K-A2 program, promoted through a partnership between four universities and three between four universities and three primary schools (6-12 years old) from Spain, Cyprus, Italy, and Portugal. It aims to generate different actions that contribute to the recognition and development of inclusive pedagogical of inclusive, creative, and innovative pedagogical practices, using digital media. media. The Institute of Social Work was one of the partners of this program. At its conclusion, we interviewed the coordinator Begoña Vigo Arrazola of Campus Iberus.